Analisis Kelalaian dalam Berdinas Jaga di Kapal MV. Andhika Kanishka pada Pelabuhan Muara Pantai saat Bongkar Muat - Nakano, Muhamad Goldy; Siregar, Muhammad Sapril; Nurman, Salfauqi (PT. PENERBIT TIGA MUTIARA, 2023)
Negligence during duty on board has a significant negative impact on loading and unloading activities. Problems in loading and unloading activities often arise due to both internal and external factors such as human error, equipment issues, and natural conditions. This study aims to investigate negligence during duty on the MV. Andhika Kanishka ship at Muara Pantai Port, focusing on the factors, consequences, and strategies for addressing it. The research was conducted using a qualitative approach, involving direct observation, in-depth interviews, and documentary analysis, and data was triangulated for analysis. The subjects for interviews included the ship's captain and crew. The research results indicate that: 1) Factors contributing to negligence are carelessness and psychological factors; 2) Consequences include errors during loading, difficulty in closing hatches and hatch covers, and cross-deck becoming dirty; and 3) Strategies for addressing negligence during duty involve maintaining communication, shifting cargo, and cleaning the ship's deck.